2021
DOI: 10.3390/polym13040662
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Mechanical Properties of Electrospun Polycaprolactone Scaffolds: Effect of Applied Voltage

Abstract: The aim of this work is to investigate the effect of the applied voltage on the morphological and mechanical properties of electrospun polycaprolactone (PCL) scaffolds for potential use in tissue engineering. The morphology of the scaffolds was characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), and the BET techniques for measuring the surface area and pore volume. Stress-strain curves from tensile tests were obtained for estimating the mechanical properties. Additional studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 66 publications
4
32
0
Order By: Relevance
“…At an applied voltage of 18 kV, the electrospun fibers appear to be slightly wet and not straight ( Figure 7 f), which is possibly caused by the low evaporation rate of DCM as a consequence of shorter electrospinning duration. Olive et al [ 42 ] studied the effect of applied voltage on electrospun fibers and found similar results. Furthermore, the results show that a 15 kV applied voltage was suitable to fabricate the electric field in the electrospinning process ( Figure 7 d).…”
Section: Resultsmentioning
confidence: 75%
“…At an applied voltage of 18 kV, the electrospun fibers appear to be slightly wet and not straight ( Figure 7 f), which is possibly caused by the low evaporation rate of DCM as a consequence of shorter electrospinning duration. Olive et al [ 42 ] studied the effect of applied voltage on electrospun fibers and found similar results. Furthermore, the results show that a 15 kV applied voltage was suitable to fabricate the electric field in the electrospinning process ( Figure 7 d).…”
Section: Resultsmentioning
confidence: 75%
“…Herrera et al studied the effect of applied voltage on the morphology and mechanical properties of PCL electrospun nanofibers. 119 This study revealed that larger fiber diameters can be obtained by increasing the voltage during electrospinning. Also, an increase in the applied voltage (to the jet solution) had an effect on the fiber diameters, surface roughness and pores volume increase as shown in Fig.…”
Section: Applied Voltagementioning
confidence: 79%
“…[98,99] On contrary, the increase in fibers' diameters with the increase of voltage was also reported by different works. [83,100,101] Regarding the feed rate, lower values are beneficial to maintain a balance between the leaving polymeric solution and replacement of that solution with a new one during jet formation. [86] On contrary, very elevated values of feed rate promote the formation of unstable jet and insufficient solvent evaporation, resulting in fibers with higher diameters and defects, and reduced deposition areas.…”
Section: Process Parametersmentioning
confidence: 99%